Culture‐independent real‐time PCR reveals extensive polymicrobial infections in hospitalized diarrhoea cases in Kolkata, India. (23rd January 2012) - Sinha, A.; SenGupta, S.; Guin, S.; Dutta, S.; Ghosh, S.; Mukherjee, P.; Mukhopadhyay, A. K.; Ramamurthy, T.; Takeda, Y.; Kurakawa, T.; Nomoto, K.; Nair, G. B.; et al.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract Culture‐independent identification of diarrhoeal aetiological agents was performed using DNA harvested from diarrhoeal stool specimens with SYBR‐Green‐based real‐time PCR targeting Vibrio cholerae, Vibrio parahaemolyticus, Campylobacter spp., Shigella spp. and three different pathotypes of diarrhoeagenic Escherichia coli. Conventional culture‐dependent methods detected bacterial enteropathogens in 68 of 122 diarrhoeal stool specimens. Of 68 specimens, 59 (86.8%) had a single pathogen and the remaining nine (13.2%) had polymicrobial infections with multiple pathogens. Re‐analysis of the 68 specimens by culture‐independent real‐time PCR methods showed that 25 (36.8%) specimens contained single pathogen and 43 (63.2%) specimens contained mixed infections with multiple pathogens. The prevalence of such high levels of polymicrobial infections would not have been detected without using real‐time PCR. Culture‐dependent analysis assigned 54 of the 122 selected archived specimens as 'no known aetiology'. However, re‐analysis of these samples by real‐time PCR showed the presence of single or multiple pathogens among 34 (63%) of these specimens. Estimation of relative pathogen load by real‐time PCR in the stool specimens indicated that the inability of conventional culture‐dependent methods to detect the pathogens was related to lower colony‐forming units of the pathogen, as reflected by lower Ct values. Detection of high levels of polymicrobial infection by real‐time PCR indicates that in the settings like Kolkata and its surroundings, where cholera and other enteric diseases are endemic, the concept of one pathogen one disease might need to be re‐evaluated.